2010
DOI: 10.4317/medoral.15.e387
|View full text |Cite
|
Sign up to set email alerts
|

Tooth-Implant connection: A bibliographic review

Abstract: The aim of this study was to carry out a bibliographic review of all available literature addressing the issue of whether or not the connection of teeth to implants by means of a prosthesis is a viable treatment alternative. Twenty articles from a variety of sources were analyzed and classified in order to draw conclusions. Articles were classified by type and an analysis was made of the different variables considered in each study, obtaining percentages of implant survival ranging from 84.4% to 100%, prosthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
0
18
0
3
Order By: Relevance
“…For example, the “Attachment systems” topic is primarily relevant for implant overdentures; however, this was not combined with the “Implant overdenture” topic, the former remaining stable over the years at 2.8% of studies, on average, the latter revealing significant decrease of scientific interest from 16.0% (2001–2004) down to 9.4% (2009–2012). The second most dramatic decrease was seen for the “Tooth‐to‐implant connection” topic (from 2.6% down to 0.4%); however, a recent review publication concluded that evidence on this treatment concept is disparate to date . It thus remains arguable whether decrease of publication frequency may actually indicate that scientific consensus has yet been reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the “Attachment systems” topic is primarily relevant for implant overdentures; however, this was not combined with the “Implant overdenture” topic, the former remaining stable over the years at 2.8% of studies, on average, the latter revealing significant decrease of scientific interest from 16.0% (2001–2004) down to 9.4% (2009–2012). The second most dramatic decrease was seen for the “Tooth‐to‐implant connection” topic (from 2.6% down to 0.4%); however, a recent review publication concluded that evidence on this treatment concept is disparate to date . It thus remains arguable whether decrease of publication frequency may actually indicate that scientific consensus has yet been reached.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic literature review was performed via the US National Institutes of Health free digital archive of biomedical and life sciences journal literature (PubMed MEDLINE) within the time period 2001 to 2012 using the key word "dental implant" and supplemented by hand searches of Clinical Implant Dentistry and Related Research (volumes [3][4][5][6][7][8][9][10][11][12][13][14], Clinical Oral Implants Research (volumes 12-23), European Journal of Oral Implantology (volumes 1-5), Implant Dentistry (volumes 10-21), International Journal of Oral and Maxillofacial Implants (volumes [16][17][18][19][20][21][22][23][24][25][26][27], and Journal of Oral Implantology (volumes 27-38). Electronic and hand searches yielded 15,695 and 5,048 publications, respectively.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…Other researchers found that nonrigid connection design is associated with more tooth intrusion and that rigid connection is better to use [2, 9, 10, 14, 20, 30, 33, 44, 48, 5052, 59, 88, 117]. In a meta-analysis of 13 previous studies, Lang et al [88] found that 5.2% of abutment teeth were affected by intrusion and this was almost always occurred when nonrigid connections were used.…”
Section: Resultsmentioning
confidence: 99%
“…The published literature demonstrates the existence of considerable controversy and debate on whether it is recommendable to splint teeth to implants [1–7]. It is widely accepted that it is less than ideal to connect rigid ankylosed implants to relatively mobile dentition [810]. However, despite their limitations, some long term clinical studies did not demonstrate adverse effects of linking natural teeth to dental implants [1116].…”
Section: Introductionmentioning
confidence: 99%
“…This includes 8,9,10 1. Implants should be splinted to natural teeth only when the teeth need support as fully integrated implants stabilize periodontally weak teeth.…”
Section: Discussionmentioning
confidence: 99%